If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1 + 2y + -5 = 3y + -9 Reorder the terms: -1 + -5 + y + 2y = 3y + -9 Combine like terms: -1 + -5 = -6 -6 + y + 2y = 3y + -9 Combine like terms: y + 2y = 3y -6 + 3y = 3y + -9 Reorder the terms: -6 + 3y = -9 + 3y Add '-3y' to each side of the equation. -6 + 3y + -3y = -9 + 3y + -3y Combine like terms: 3y + -3y = 0 -6 + 0 = -9 + 3y + -3y -6 = -9 + 3y + -3y Combine like terms: 3y + -3y = 0 -6 = -9 + 0 -6 = -9 Solving -6 = -9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 0.20(6)+0.05x=0.10(24+x) | | 3x(x-2)(2x+1)=0 | | -99-8=7x+21 | | 7-10x=131-38x | | 103-3x=15x+23 | | .44y^2+1=0 | | 3(y+2)-2=2(4-y) | | 3(y+2)-2=2(41y) | | 5s-19s=28 | | 4t+3=t-18 | | 8+2x*3=x*4+12 | | a^2x+3x=2a^2 | | x^2-5.75+7.75=6 | | x^2-5.75+7.75=1 | | x^2-5.75+7.75=4 | | x^2-5.75+7.75=2 | | 2x^2-4x+8.8=2 | | 2x^2-4x+18.2=2 | | 5a^2-6a=1 | | (10b-6)-3(3b+2)=-3 | | x^2-8x+15.75=0 | | y=0(0)-7 | | (4y+9)(4y+9)=64y^3+432y^2+972y+729 | | 5c+6=2-y | | 5x+6x+3+8=3x+5+7x | | 16+-8-9= | | z^2-8z-20= | | 3(Q-6)=2(2Q+7)+10 | | 25+-15-12= | | 15x^2+5x-20= | | y=18(0)+0 | | 9y^2+21y+6= |